2015
DOI: 10.1016/j.bios.2015.03.042
|View full text |Cite
|
Sign up to set email alerts
|

Highly amplified detection of visceral adipose tissue-derived serpin (vaspin) using a cognate aptamer duo

Abstract: A cognate aptamer duo for visceral adipose tissue-derived serpin (vaspin) which distinctively bind to two different sites on vaspin with high affinity and specificity were successfully developed by using graphene oxide-based systematic evolution of ligands by exponential enrichment (GO-SELEX), which offers immobilization-free screening of aptamers. The specific and simultaneous bindings of this aptamer duo (V1 and V49 aptamers) to the different sites of vaspin were confirmed by circular dichroism (CD) analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…ssDNAs that were adsorbed on the rGO surface were eluted through treatment with the target compound. According to literature reports, the conformation of the aptamer changes after binding with target and by weakening the π‐π stacking interactions with rGO . This process was repeated for five rounds.…”
Section: Resultsmentioning
confidence: 99%
“…ssDNAs that were adsorbed on the rGO surface were eluted through treatment with the target compound. According to literature reports, the conformation of the aptamer changes after binding with target and by weakening the π‐π stacking interactions with rGO . This process was repeated for five rounds.…”
Section: Resultsmentioning
confidence: 99%
“…Most recently, simpler SPR signal enhancement was achieved for thrombin detection using core-shell gold capped magnetic nanoparticles (GMPs) conjugated with thrombin secondary aptamer, resulted in the LOD as low as 0.1 nM (Chen et al, 2015). Moreover, Gu's research group has demonstrated ultrasensitive detection of visceral adipose tissue derived serpin (Vaspin) and even to virus target, the bovine viral diarrhea virus type 1 (BVDV type 1), in which the AuNPs functionalized with thiol-modified secondary aptamers were used as the SPR amplification probe, thus resulting in LOD down to 3.5 ng/ml for Vaspin (Ahmad Raston and Gu, 2015) and 800 copies/ml for BVDV type 1 detection (Park et. al., 2013).…”
Section: Surface Plasmon Resonance (Spr)-based Aptasensorsmentioning
confidence: 98%
“…In addition, the most recent success in the cognate generation of dual aptamers, which is known to be possible due to the success of aptamer screening without target immobilization, has resulted in opening the use of a sandwich-type sensing platform (Ahmad Raston and Gu, 2015;Park et al, 2014). The advantages of using dual aptamers in aptasensors should be as follow; 1) easy and highly amplified signals can be generated from the use of the secondary signaling aptamer, 2) sandwich-type stable platforms can be definitely adopted, which has been known to be one of the weak points using an aptamer, and 3) the realization of aptasensors in markets are now very close, (Zhang et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…N. Hanun et al presented a sandwich-type aptasensor for detection vaspin using aptamer pair [14]. As a first vaspin binding aptamer duo, this pair of aptamers was developed by immobilization-free GO-SELEX method.…”
Section: The Sandwich-type Aptasensors Using a Pair Of Aptamersmentioning
confidence: 99%
“…GO-SELEX is based on a phenomenon that single strand DNAs adsorbed to graphene oxide surface strongly by π - π stacking. Successful screening of aptamer pairs for one protein target and two kinds of virus targets were reported based on the use of GO-SELEX so far [1214]. Another SELEX method for aptamer pair is multivalent aptamer isolation SELEX (MAI-SELEX) [19].…”
Section: Introductionmentioning
confidence: 99%